Patient global assessment and inflammatory markers in patients with idiopathic inflammatory myopathies - A longitudinal study - Lodin, Karin; Espinosa-Ortega, Fabricio; Dastmalchi, Maryam; Vencovsky, Jiri; Andersson, Helena; Chinoy, Hector; Lilleker, James B; Shinjo, Samuel Katsuyuki; Maurer, Britta; Griger, Zoltan; Ceribelli, Angela; Torres-Ruiz, Jiram; et al. (Seminars in arthritis and rheumatism, 2024)
AIM: To explore if patient global assessment (PGA) is associated with inflammation over time and if associations are explained by other measures of disease activity and function in patients with idiopathic inflammatory myopathies (IIM). METHODS: PGA and systemic inflammatory markers prospectively collected over five years were retrieved from the International MyoNet registry for 1200 patients with IIM. Associations between PGA, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP) and creatine kinase (CK) were analyzed using mixed models. Mediation analysis was used to test if the association between PGA and inflammatory markers during the first year of observation could be explained by measures of disease activity and function. RESULTS: PGA improved, and inflammatory markers decreased during the first year of observation. In the mixed models, high levels of inflammatory markers were associated with worse PGA in both men and women across time points during five years of observation. In men, but not in women, the association between elevated ESR, CRP and poorer PGA was explained by measures of function and disease activity. With a few exceptions, the association between improved PGA and reduced inflammatory markers was partially mediated by improvements in all measures of function and disease activity. CONCLUSION: Increased levels of systemic inflammation are associated with poorer PGA in patients with IIM. In addition to known benefits of lowered inflammation, these findings emphasize the need to reduce systemic inflammation to improve subjective health in patients with IIM. Furthermore, the results demonstrate the importance of incorporating PGA as an outcome measure in clinical practice and clinical trials.
Keywords: krevní sedimentace; Female; Blood Sedimentation; Inflammation; Humans; ženské pohlaví; longitudinální studie; mužské pohlaví; Male; lidé; Longitudinal Studies; Myositis; Outcome Assessment, Health Care; myozitida; zánět; hodnocení výsledků zdravotní péče